ARCHITECTURE ECOLOGY IN TECHNOLOGY CENTER DESIGN OF AEROPONIC AGRICULTURAL IN MALANG - Wardana, Ardhi Sukma; Kusumadewi, Tarranita; maslucha, luluk (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.524, 2017)
Technology Center Design of Aeroponic Agricultural is a container or means for researching and developing cultivation by means of aeroponic system to maximize result, quantity and quality of crop products that can be utilized by the general public, students, researchers and farmers to obtain learning and training. The approach to this design uses architecture ecology that serves to avoid harm to ecosystems, biodiversity, and humans. This approach responds to the design of utilities, energy supply, social, and human behavior so that the results of such an application will be able to prevent human caused natural disasters. In addition, this approach is applied to preserve the surrounding environment, produce the best agricultural products and improve environmentally conscious farming.